2019
DOI: 10.3389/fevo.2019.00342
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Genome–on Selective Constraints and Signatures at the Organism, Cell, and Single Mitochondrion Levels

Abstract: Natural selection acts on the phenotype. Therefore, many mistakenly expect to observe its signatures only in the organism, while overlooking its impact on tissues, cells and subcellular compartments. This is particularly crucial in the case of the mitochondrial genome (mtDNA), which, unlike the nucleus, resides in multiple cellular copies that may vary in sequence (heteroplasmy) and quantity among tissues. Since the mitochondrion is a hub for cellular metabolism, ATP production, and additional activities such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 100 publications
1
45
0
Order By: Relevance
“…The involvement of two genomes to produce a functional and stable protein further indicates an evolutionary link between genetic drift and mitochondrial translation. Our experimental finding therefore illustrates the requirement of tight mito-nuclear coevolution to maintain mitochondrial activities ( Shtolz and Mishmar, 2019 ; Mishmar, 2020 ).…”
Section: Resultssupporting
confidence: 61%
“…The involvement of two genomes to produce a functional and stable protein further indicates an evolutionary link between genetic drift and mitochondrial translation. Our experimental finding therefore illustrates the requirement of tight mito-nuclear coevolution to maintain mitochondrial activities ( Shtolz and Mishmar, 2019 ; Mishmar, 2020 ).…”
Section: Resultssupporting
confidence: 61%
“…Because of the very low frequency of these mutations in contrast to the high copy number of mtDNA (hundreds to around 200,000 copies, with an average of 1–10 mtDNA copies per mitochondrion in mature oocytes [ 16 , 82 ]), mutations in one or a few mtDNA molecules are not expected to have noticeable functional consequences for a cell compared with mutations in the nuclear genome. However, at a single-mitochondrion level, they might have a functional impact ([ 83 ], reviewed in [ 84 ]). In contrast, negative selection was demonstrated for high-allele-frequency mtDNA mutations in the mouse germline (reviewed in [ 85 ]), and it was suggested that purifying selection does not act directly on oocytes but rather on cells during postimplantation development [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almost in all cases, nuclear DNA is used to describe the signature of selection, while ignoring its effect on the tissue, cells, and subcellular compartments. This is very crucial for mitogenome, which in contrast to the nucleus, serves as a powerhouse for the cell and are present in multiple copies in the cytoplasm that may vary in sequence (heteroplasmy) and quantity among tissues [ 20 ]. Each mitochondrion is maternally inherited and codes for enzymes that are mainly involved in cellular bioenergetics [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each mitochondrion is maternally inherited and codes for enzymes that are mainly involved in cellular bioenergetics [ 21 ]. As it is a vital compartment for the generation of cellular metabolism, including ATP production, nucleotide biosynthesis, and other activities, any dysfunction will lead to tissue and systemic disorders [ 20 ]. Therefore, strong purifying negative selection acts to remove deleterious mutations, and in parallel, positive selection acts on the mitochondria to promote adaptation of cells, and in return the whole organism, to environmental and physiological changes [ 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%